Complete Short Works of George Meredith - Meredith, George, 1828-1909 (Salt Lake City, UT : Project Gutenberg, 2004)
"Complete Short Works of George Meredith" by George Meredith is a collection of short stories and prose written during the late 19th century. This anthology encompasses a variety of tales that delve into themes like romance, adventure, and social commentary, showcasing Meredith's unique narrative style and rich characterizations. The opening story, (3z(BFarina,(3y (Bintroduces readers to rich historical settings and characters, particularly focusing on the merchant Gottlieb von Groschen and his daughter, Margarita, as they navigate the complexities of love, honor, and societal expectations. The opening of (3z(BFarina(3y (Bsets the stage in Cologne during an enchanting yet dangerous time, where the fortunes of a wealthy merchant, Gottlieb, and the affections of his beautiful daughter, Margarita, become the center of youthful rivalry and chivalric exploits. The narrative unfolds with a lively depiction of the (3z(BWhite Rose Club,(3y (Ba group of young men who vie for Margarita$1 (Bs attention, resulting in humorous and competitive encounters. As the story progresses, the tension mounts with the appearance of the menacing Baron Werner$1 (Bs band, indicating that love and danger are intricately woven into the fabric of this tale, foreshadowing an exciting mix of romance and adventure that characters like Farina, a brave outsider, and the young men of the club will experience. (This is an automatically generated summary.)s
Release date is 2004-11-05
Produced by David Widger
Keywords: English fiction -- 19th century